Hakimiyyah dan Ideologi Jihad Perspektif Sayyid Qutb - Unsi Andal Bara (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2026)
This study examines Sayyid Qutb's concept of hakimiyyah and jihad ideology in the context of resistance against the secular regime in Egypt, highlighting the interrelationship between Qutb's views on hakimiyyah - God's sovereignty - and jihad as a means of political struggle against a secular government that is considered not sharia-based. Using a qualitative-descriptive method and textual analysis of Qutb's major works such as Milestones, this study finds that hakimiyyah became the basis of Qutb's rejection of the secular system which he called a new form of jahiliyyah, while jihad was understood as a physical revolution to overthrow the anti-shariah regime. In conclusion, Qutb's thoughts on hakimiyyah and jihad have had a major influence on the development of radical Islamic movements that seek to establish an Islamic state based on sharia law, relevant in the study of modern Islamic political thought and resistance to secularism in the contemporary Muslim world. Keywords: jihad, hakimiyyah, Islam, government, politics. political philosophy, Islamic reform.